2017
DOI: 10.1002/brb3.706
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in brain‐derived neurotrophic factor at plasma level but not in serum concentrations in suicide behavior: A systematic review and meta‐analysis

Abstract: IntroductionSuicide is known as a major health concern worldwide. There is evidence for the role of brain‐derived neurotrophic factor (BDNF) in suicide behavior. Therefore, this factor has been proposed as a biomarker for suicide behavior. Clinical studies have measured BDNF concentrations at central and peripheral levels. As a consequence, the aim of this study was to assess BDNF levels in blood plasma and serum to see whether there is a difference in concentrations in patients with suicide behavior when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…Importantly, the authors found no confounding effects of age, gender, brain pH, time between death and analysis, or antidepressant treatment. Although this study should be considered preliminary evidence as it is a small sample and the first study to examine these relationships among youth, its results match those found with adults (Salas‐Magaña et al., ), and dovetail nicely with studies on the relationship between stress and suicide among youth (e.g. Giletta et al., ).…”
Section: Potential Etiology: Risk Factors and Correlatessupporting
confidence: 75%
“…Importantly, the authors found no confounding effects of age, gender, brain pH, time between death and analysis, or antidepressant treatment. Although this study should be considered preliminary evidence as it is a small sample and the first study to examine these relationships among youth, its results match those found with adults (Salas‐Magaña et al., ), and dovetail nicely with studies on the relationship between stress and suicide among youth (e.g. Giletta et al., ).…”
Section: Potential Etiology: Risk Factors and Correlatessupporting
confidence: 75%
“…The role of BDNF in both pathophysiology and therapy of depressive disorders seems to be strongly confirmed [ 50 , 51 ]. Similarly, the relationship between BDNF and suicidal behavior is well documented [ 3 , 19 , 20 , 52 ]. Most published data indicate a significant decrease in BDNF levels in suicides, which is why our observations are consistent with previous studies [ 3 , 19 , 20 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although BDNF seems to be a promising marker of suicidal behavior, it should be remembered that its expression in various tissues (including brain) may be region-specific [3,19,20]. Similarly, some differences between blood components were observed in suicides [52]. Altered BDNF level in suicides may be the consequence of persistent (like Val66Met polymorphism) or variable genome changes (like higher methylation status in BDNF gene promoter or changed histone code due to post-translational changes in chromatin) (see [55]).…”
Section: Plos Onementioning
confidence: 99%
“…Our study has several limitations. We assessed serum BDNF, and peripheral BDNF has an uncertain relationship with brain levels of BDNF (Kim et al, 2007;Salas-Magaña et al, 2017). The origins of serum BDNF levels are still uncertain and it is suggested to be derived from platelet stores and vascular endothelial cells as well as from neurons and glial cells in the brain if it crosses the blood-brain barrier (Guo et al, 2008;Kim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%